Packinghouse Citrus Black Spot ID / Identificación de la Mancha Negrade los Cítricos en las Plantas de Procesamiento - Mark Ritenour; Megan M. Dewdney; Natalia A. Peres; Jamie D. Yates (EDIS, 2010)
HS1184, a one-page identification sheet in English and Spanish by Mark Ritenour, Megan Dewdney, Natalia Peres, and Jamie Yates, assists packinghouse graders in the detection of citrus black spot. Published by the UF Department of Horticultural Sciences, August 2010.